FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN RUMAH SEBAGAI TEMPAT PERSALINAN DI PUSKESMAS SIGAMBAL KABUPATEN LABUHANBATU TAHUN 2020 - novica jolyarni (Jurkessutra : Jurnal Kesehatan Surya Nusantara, 2021)
ABSTRACTThe labor process is faced with a critical condition for the problem of emergency labor, so it is expected that labor is carried out in a health facility. This study aims to factor factors related to the selection of houses as a place of birth in the working area of Sigambal Public Health Center, South Labuhanbatu Regency in 2019. The type of research used in this study is analytic observational research. The population in this study were all mothers who had given birth at home in the work area of Sigambal Public Health Center, South Labuhanbatu Regency from March to December 2018 as many as 46 people. Samples were taken using total sampling, namely the entire population into samples. The instrument used was a questionnaire of factors in choosing a house as a place of delivery. The results of the bivariate analysis show there are 3 independent variables that are statistically related, namely the income, knowledge and attitude variables with p-value 0.05 The conclusion of this study is that knowledge, attitudes and income are proven to be factors that are related to the choice of home as a place of birth. It is suggested to need cooperation between the SIGAMBALVillage Head and community leaders, religious leaders, village midwives and Sigambal Community Health Center to develop village regulations that must be delivered in health facilities. . Keywords: Factors, Selection of Houses and Maternity Places